2015
DOI: 10.15439/2015f322
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the performance and energy consumption of AES in wireless sensor networks

Abstract: Abstract-With WSN deployments increasing in popularity, securing those deployments becomes a necessity. This can be achieved by encrypting inter-node communications and/or using message authentication codes. AES is a well studied symmetric cipher, with no known practical vulnerabilities, that can be used to solve both problems. We provide an optimized implementation of AES, with four modes of operation (ECB, CBC, CFB and CTR), that uses the hardware accelerator available on the ATmega128RFA1 microcontroller, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The current sensing resistors used in the research by Lee et al [30] and Panait et al [31], differ from the one employed in this research being (1Ω). Lee et al [30] and Panait et al [31] make use of 10.1Ω and 4.99Ω resistors respectively. In addition to this, Panait et al [31] test the energy consumption of only AES implementations in different modes of operations.…”
Section: Previous Workmentioning
confidence: 90%
See 1 more Smart Citation
“…The current sensing resistors used in the research by Lee et al [30] and Panait et al [31], differ from the one employed in this research being (1Ω). Lee et al [30] and Panait et al [31] make use of 10.1Ω and 4.99Ω resistors respectively. In addition to this, Panait et al [31] test the energy consumption of only AES implementations in different modes of operations.…”
Section: Previous Workmentioning
confidence: 90%
“…In this research a much smaller resistance is used for the current sensing resistor to ensure less wasted power, striving for a higher precision result. Panait et al [31] Panait et al measure a device based on the ATmega128RFA1 microcontroller. They conduct measurements on current and execution time of AES in ECB, CBC, CFB and CTR modes.…”
Section: Previous Workmentioning
confidence: 99%
“…Result have shown that on encrypting data, hardware implementation of AES is the fastest; further in the work of [19] and [20], the result shows that hardware implementation of AES has a better throughput and more energy efficient. Similarly in the work of [21], when compared to AES software implementation it was justified by the result of their experiment that AES hardware implementation has lesser energy consumption and performs faster.…”
Section: Related Literaturementioning
confidence: 99%
“…A sensor device using the MICAz with 4 KB RAM (Crossbow Technology, San Jose, CA, USA) and 7-MHz ATmega128L microcontroller (Microchip Technology Inc, Chandler, AZ, USA) and a smart phone using an iPhone 6s (Apple, Cupertino, CA, USA) with 2 GB RAM ARM (armv8-a) CPU. The data are taken from [13,24,25] for the time required on the MICAz while we implement those implementations on a smart phone using the Pairing Based Cryptographic Library [26]. The result is summarized in Table 2.…”
Section: C1mentioning
confidence: 99%